Electrocatalytic Epoxidation of Olefins Using Iron(III) Tetraphenylporphyrin Chloride - Khorasni-Motlagh, M.; Noroozifar, M.; Torabi, A.-N. (Asian Journal of Chemistry, 2010)
Electrocatalytic epoxidation of olefins by using iron-porphyrin complex, iron(III) tetraphenylporphyrin chloride, as a mediator in an acetone aqueous Na2SO4 two phase system was performed successfully in an one-compartment cylindrical cell under constant potential condition. The epoxidation reactions have been monitored by gas chromatographic analysis. Optimization of the electrolysis conditions and estimation of the reaction mechanism are discussed.